2016
DOI: 10.1073/pnas.1611477113
|View full text |Cite|
|
Sign up to set email alerts
|

Brassinosteroids participate in the control of basal and acquired freezing tolerance of plants

Abstract: Brassinosteroids (BRs) are growth-promoting plant hormones that play a role in abiotic stress responses, but molecular modes that enable this activity remain largely unknown. Here we show that BRs participate in the regulation of freezing tolerance. BR signaling-defective mutants of Arabidopsis thaliana were hypersensitive to freezing before and after cold acclimation. The constitutive activation of BR signaling, in contrast, enhanced freezing resistance. Evidence is provided that the BR-controlled basic helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
146
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 42 publications
5
146
0
2
Order By: Relevance
“…Brassinosteroids (BRs) are a widespread group of plant hormones that play a crucial role during plant growth and development (Wang et al ). Furthermore, BRs play a role in abiotic stress responses, such as drought, low temperature, freezing tolerance and heavy metal contamination (Kagale et al , Fowler and Thomashow , Eremina et al , Rajewska et al ). Several recent studies also revealed that BRs participate in pathogen defense responses (Heese et al , Albrecht et al , Belkhadir et al , Wang ), and brassinolide (BL) could induce disease resistance both in tobacco and rice (Nakashita et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Brassinosteroids (BRs) are a widespread group of plant hormones that play a crucial role during plant growth and development (Wang et al ). Furthermore, BRs play a role in abiotic stress responses, such as drought, low temperature, freezing tolerance and heavy metal contamination (Kagale et al , Fowler and Thomashow , Eremina et al , Rajewska et al ). Several recent studies also revealed that BRs participate in pathogen defense responses (Heese et al , Albrecht et al , Belkhadir et al , Wang ), and brassinolide (BL) could induce disease resistance both in tobacco and rice (Nakashita et al ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several transcriptional regulators of the CBF s have been identified, including ICE1/2 (Inducer of CBF expression), MYB15, CAMTA3 (Calmodulin‐binding transcription activator 3), EIN3 (Ethylene insensitive 3), SOC1 (Suppressor of overexpression of co 1), PIF3/4/7 (Phytochrome‐interacting factors), CCA1 (Circadian clock associated 1), LHY (Late elongated hypocotyl), BZR1 (Brassinazole‐resistant 1)/BES1 (BRI1‐EMS suppressor 1), and CESTA (Chinnusamy et al ; Agarwal et al ; Doherty et al ; Fursova et al ; Seo et al ; Dong et al ; Lee and Thomashow ; Shi et al ; Eremina et al ; Jiang et al ; Li et al ) (Figure ).…”
Section: Transcriptional Regulation Of the Cbfs In The Cold‐signalingmentioning
confidence: 99%
“…The components of BR (brassinosteroid) signaling are reported to positively regulate the cold‐induced transcription of the CBF s (Eremina et al ; Li et al ). BZR1, BES1, and CES (CESTA) are the key positive regulators of the BR response (He et al ; Yin et al ), and recent studies revealed that these transcription factors directly bind to the E‐box and BRRE binding sites of the CBF1 and CBF2 promoters, positively regulating their expression (Eremina et al ; Li et al ).…”
Section: Transcriptional Regulation Of the Cbfs In The Cold‐signalingmentioning
confidence: 99%
See 2 more Smart Citations